Maternal Gestational Diabetes and Autism Spectrum Disorder in Offspring: Risk Factors, Mechanisms, and Pediatric Implications - Maryam, Rasha; Fayaz, Zyna; Musthafa, Nafila; Abdul Jaleel, Jasna; Bahutair, Shadha Nasser Mohammed; Salama, Rasha Aziz Attia; Patni, Mohamed Anas (Dubai Medical Journal, 2025)
Introduction: Gestational diabetes (GDM) complicates around 14% of pregnancies globally. While GDM’s physiological effects are often transient, its long-lasting effects on the mother and the child are significant. Studies show a heightened chance of autism occurring in offspring subjected to gestational diabetes in utero. Methods: A thorough search of literature was performed across PubMed, SCOPUS, and ProQuest, identifying 35 relevant studies published between 2012 and 2024. This review focuses on exploring the impact of GDM on the offspring’s chances of developing autism. It aims to explore the factors influencing this relationship, such as the timing of GDM onset, the presence of coexisting complications, and the condition’s underlying mechanisms. Results: The findings demonstrate that gestational diabetes can significantly increase the risk of autism. Key factors influencing this relationship include the timing of diagnosis, maternal glucose management, and treatment strategies during pregnancy. Potential mechanisms include increased fetal exposure to inflammation, oxidative stress, and immune dysregulation. Conclusion: The findings highlight the importance of early and effective GDM management and its pediatric implications for improving neurodevelopmental outcomes in offspring during early childhood.